Pengaruh Pemberian Ekstrak Buah Plum (Prunus domestica L.) Terhadap Panjang Badan Fetus Tikus Putih (Rattus novergicus) Galur Sprague Dawley Pada Tikus Putih (Rattus novergicus) Hamil Yang Dipapar Alkohol - Dewi Tri Atmaningsih; Rodiani Rodiani (CV. Jasa Sukses Abadi, 2023)
Alcohol consumption during pregnancy cause fetal alcohol syndrome and increases oxidative stress. Plum contains polyphenols as an antioxidant which can prevent oxidative stress by affecting the activity of osteoblasts and osteoclasts. This study aims to determine the effect of plum extract (Prunus domestica L.) on body length of fetal white rats (Rattus norvegicus) Sprague Dawley strain in pregnant white rats exposed by alcohol. This research used 30 white female rats of Sprague Dawley strain which divided into 5 groups. The positive control (KP) not given treatment, the negative control (KN) was given alcohol 0,27 ml/day on the 6th-15th day of pregnancy, the treatment group (P1, P2, P3) was given alcohol 0,27 ml/day and plum extract with respective dose 0f 40, 80, 160 mg orally for 21 days of gestation. Then the fetus was taken surgically on 21 days of gestation. This research showed that the average length of KP=41,34; KN=38,67; P1=39,22; P2=39,65; and P3=40,02 in mm. Then, the data were tested by One Way Anova test and resulting p value<0,05 and F count>F table for all data, then it followed by post hoc LSD test and the results showed p value<0,05 on measurements of body length except on KN-P1, P1-P2, dan P2-P3. There was effect of plum extract (Prunus domestica L.) on body length of fetal white rats (Rattus norvegicus) Sprague Dawley strain in pregnant white rats exposed by alcohol.